ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE FULL COSTING PADA UD. ALVINA FOOD SURABAYA - Adham Pramedya Ardhiansyah; Iman Karyadi (CV. Denasya Smart Publisher, 2026)
Accurate determination of the cost of production is essential for supporting pricing decisions and profit calculation. UD. Alvina Food Surabaya applies a simple method in calculating the cost of production by summing all production costs and dividing them by the number of units produced, resulting in several production cost components not being fully recognized. This study aims to analyze the cost of production calculation applied by UD. Alvina Food Surabaya and compare it with the Full Costing method. The research employed a descriptive quantitative approach. Data were collected through observation, interviews, and documentation related to the company's production costs. The analysis was conducted by calculating the cost of production using both the company's method and the Full Costing method, followed by a comparison of the results. The findings indicate that the cost of production of uncooked rengginang based on the company's method was IDR 16,575 per pack, while the Full Costing method resulted in IDR 18,548 per pack. Meanwhile, the cost of production of cooked rengginang based on the company's method was IDR 10,750 per pack, whereas the Full Costing method produced IDR11.740 The difference in calculation results was mainly caused by the inclusion of factory overhead costs that had had not previously been considered by the company, particularly depreciation expenses related to production equipment, operational vehicles, and production buildings. By incorporating all production cost components, the Full Costing method provides a more comprehensive cost of production and can serve as a more accurate basis for pricing decisions and profit determination.